Web-based GIS for public participation in urban planning and management - Yaakup, Ahris; Jama'an, Jaafar; Abu Bakar, Yazid; Sulaiman, Susilawati (2001)
Public participation in urban planning is needed as a means of improving information and to facilitate the adaptability of the system. In Malaysia, the preparation of the development plan called for participation as a value consensus mechanism, not only from the public at large but other agencies to allow data sharing and to ensure more informed decision. Geographic Information System data which were made accessible on the Internet by web-based GIS technology offered an effective medium for public participation. Its platform-independent and display-only map creation interface provides a good browsing facility for potential data consumers. The data conversion capabilities of GIS were used to demonstrate the possibility of sharing the data in different formats, particularly the Spatial Data Transfer Standard format. Presentation of spatial data using image maps allows users to reach particular data sets quickly and efficiently. These interfaces demonstrate the capacity to view, manipulate and distribute geographic data via WWW in an efficient, organised and user-friendly manner. Public can have access to these information and be more informed of the planning activities that are taking place. Other agencies can assist in developing a better database which consequently enhance the decision making process. The Web-Based GIS for Klang Valley region is now being developed to include tables and map based information for all the applications developed in the system. The web-based GIS developed consists 10 applications including Population and Socio-economic, Land Use, Tourism, Industry and Commerce, Environment, Traffic and Transportation, Utilities and Public Amenities, Green and Recreational Areas, Housing and Squatter Settlements and Geohazard. The operations offered a means for the users to display maps, submit query as well as display data sources and data structure base on selected maps. This application has several useful visualisation functions that are appropriate for Public Participation through interactive uses such like Zoom In, Zoom Out, Pan, Hyper Link, Full Extension, Identify and Simple Query.